Development of standard operating procedure and standardization of Habb-e-Banafsha Qawi-A Unani polyherbal formulation - Athar Ali; Sabiha Sumbul; Malik Mobeen Ahmad; Sayeed Ahmad; Hifzul Kabir; M Z Abdin (Wolters Kluwer Medknow Publications, 2015)
Introduction: Herbals drugs became a boon for mankind since ancient times and still are used worldwide for the treatment of various human ailments. The safety of alternative medicinal preparations has been questioned due to reports of unwanted side effects. To maintain the quality and efficacy of these drugs, it is essential to standardize them in order to avoid the use of substandard or adulterated medicines in the market. Unani system of medicine mainly focuses on the treatment by natural drugs. Habb-e-Banafsha Qawi is useful in a cough, catarrah, and coryza. Materials and Methods: Physiochemical constants of Habb-e-Banafsha Qawi were determined through organoleptic characters, macro- and micro-scopic characters, ash value, solubility, pH values. Chromatographic fingerprints were developed using thin layer chromatography method. Aflatoxin (AF) contamination, heavy metal, and pesticide residues were also evaluated by standard methods.Objectives: In the present study, an attempt has been made to develop standard operating procedure and physiochemical parameters to monitor the quality of a Unani poly-herbal formulation, Habb-e-Banafsha Qawi. Results: The tablets tasted sweetish bitter with a pleasant odor, water soluble and acidic in nature. Rfvalues were almost same in all the extracts. No AF, heavy metal, and pesticide residues were observed. Conclusions: It may be concluded that the values and chromatographic fingerprints obtained can be used for quality evaluation and to set new pharmacopoeial standards for the preparation of Habb-e-Banafsha Qawi.